2014
DOI: 10.1002/etc.2682
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic and genotoxic effects of metalaxy‐M on earthworms (Eisenia fetida)

Abstract: As the main optical isomer of metalaxyl, metalaxyl-M has been widely used worldwide in recent years because of its notable effect on the prevention and control of crop diseases. Together with the toxicity and degradation of metalaxyl-M, the chemical has attracted the attention of researchers. The present study examined the toxic effects of metalaxyl-M on earthworms at 0 mg kg(-1) , 0.1 mg kg(-1) , 1 mg kg(-1) , and 3 mg kg(-1) on days 7, 14, 21 and 28 after exposure. The results showed that metalaxyl-M could c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…Malondialdehyde is considered to be the major peroxidation product of the reaction between free radicals and unsaturated fatty acids in cells . The content of MDA can indicate the level of lipid peroxidation . In the present study, [C 8 mim]Cl had little influence on the MDA content on day 7.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Malondialdehyde is considered to be the major peroxidation product of the reaction between free radicals and unsaturated fatty acids in cells . The content of MDA can indicate the level of lipid peroxidation . In the present study, [C 8 mim]Cl had little influence on the MDA content on day 7.…”
Section: Discussioncontrasting
confidence: 49%
“…The results in Table 1 show that both the [C 8 mim]Cl dose and exposure time caused extremely significant changes in all of the biomarkers of the earthworms. In addition, a significant interaction between the [C 8 mim]Cl dose and exposure time was observed, which indicated that changes in the biomarkers of the earthworms might result from the combined effects of dose and time [18]. The results from the post hoc least significant difference test after two-way ANOVA ( Table 2) revealed that a significant difference exists between the [C 8 mim]Cl treatments and the controls on the levels of ROS; activities of CAT, POD, and GST; and DNA damage.…”
Section: Two-way Anova Results For Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Catalase activity may increase when earthworms are subjected to mild stress, but generally, it decreases under severe stress (Liu et al 2014). This explains the trend in CAT activity observed in non-biochar-amended substrates.…”
Section: Catalasementioning
confidence: 95%
“…Oxidative stress occurs due to an imbalance between the generation and removal of ROS by the antioxidant system defense. 30 According to the previous study, the hydroxyl radicals (•OH) were the most effective ROS. 31 The ability of inhibition of hydroxyl radicals (IHR) was used to measure the •OH content indirectly, which account for the oxidative stress stemmed from pollutants.…”
mentioning
confidence: 99%